Integrating Body Schema and Body Image in Neurorehabilitation: Where Do We Stand and What’s Next? - Rocco Salvatore Calabrò (Brain Sciences)
Given the widespread debate surrounding the definitions and functional roles of “Body Schema” and “Body Image”, these constructs have become central to understanding motor control and rehabilitation, particularly for individuals with neurological impairments [...]